Hydroalcoholic Extracts Effect of Rosa damascena Mill and Anethum graveolens on the Proteins Glycosylation In Vitro - M Soleimani; K Shahanipour (Institue of Medicinal Plants, ACECR, 2017)
Background: One of the complications of diabetes mellitus is "proteins glycosylation in the body" causing the change in nature, structure and biochemical activity of them. Decreasing or inhibiting this reaction causes to improve diabetic symptoms. The use of antioxidant-rich herbs in this case, seems to be effective. Objective: The purpose of this study is to investigate the albumin and hemoglobin glycosylation reaction in the presence of various concentrations of Anethum graveolens and Rosa damascena Mill hydroalcoholic extracts. Methods: 1) plants collection, 2) extraction by maceration method, 3) evaluating the total antioxidant capacity and phenole amount respectively by DPPH and folin-Ciocalteu method, 4) specializing and measuring the amount of hemoglobin from human blood, 5) optimizing the stabilization, 6) investigating the glycosylation amounts, both in the presence and absence of extracts.  Results: According to results obtained, the phenol amount and the total antioxidant capacity of Anethum graveolens hydroalcoholic extract is significantly more than Roseschr('39')s (P<0.05). The highest amount of hemoglobin glycosylation per time unit, has been at a concentration of 10 mgr glucose for 72 hours of incubation and about albumin was 30 mgr within 72 hours. For both extracts in concentration 0.1µg / ml of both proteins, the Anethum graveolens hydroalcoholic extract functions better compared to Rosa damascena Mill (P <0.05). Conclusion: The two Anethum graveolens and Rosa hydroalcoholic extracts on average cause to reduce albumin and hemoglobin glycosylation. But more studies are needed to prove it.